PENERAPAN METODE CERTAINTY FACTOR PADA SISTEM PAKAR DIAGNOSA PENYAKIT TANAMAN CABAI - Pradana, Windu Adi; Saputri, Tri Aristi (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
Chili is an agricultural plant that has a characteristic taste, however, most people in Indonesia really like it to be consumed, because it can increase appetite and also has a lot of content in it, Chili can also be classified as a vegetable or seasoning. As a spice, very spicy chilies are a flavor enhancer for a food. Chili is a commodity that is very much cultivated by farmers in Indonesia because it has a high selling price and has many uses for health, one of which is containing anticancer substances. Chili plants are suitable to be planted in humus soil, and are slightly loose, there is also no potential for stagnant water, and in their care must be considered carefully, and on that basis the author tries to observe and understand what diseases usually attack chili plants, with various symptoms, by using Certainty Factor method in determining the type of disease and what the solution is. using a value that indicates the level of expert confidence in the data. Certainty Factor uses the concept of belief and uncertainty. The author conducted a literature study and interviews as a method for data collection. For the results of various data collections, then the results of these data are applied and adjusted in the rules of the Certainty Factor method, and the result is that the authors get the results of a high enough level of certainty to determine the type of disease with the existing symptoms, which ranges from 85 -90%. And with these calculations the author can inform the results of this study to chili farmers. Because farmers often encounter problems when cultivating chili plants, various diseases that attack chili plants include Fusarium wilt, Ralstonia wilt, fruit rot, yellow virus, leaf spot. With various characteristics that have been described, then with various references the author looks for solutions that can be applied by farmers so that crop yields are maximized so as to help improve the economy in Indonesia. With this research, chili farmers can carry out treatment, counseling and prevention from an early age.